2010
DOI: 10.1111/j.1365-2141.2010.08303.x
|View full text |Cite
|
Sign up to set email alerts
|

research paper: Role of the cold shock domain protein A in the transcriptional regulation of HBG expression

Abstract: Summary Impaired switching from fetal haemoglobin (HbF) to adult globin gene expression leads to hereditary persistence of fetal haemoglobin (HPFH) in adult life. This is of prime interest because elevated HbF levels ameliorate β‐thalassaemia and sickle cell anaemia. Fetal haemoglobin levels are regulated by complex mechanisms involving factors linked or not to the β‐globin gene (HBB) locus. To search for factors putatively involved in the expression of the γ‐globin genes (HBG1, HBG2), we examined the reticulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…ChIP experiments were performed with HIF-2α (Novus Biologicals) or immunoglobulin G (IgG) antibody (Santa Cruz) as previously described [20], [21] except that immuno-complexes were washed using high-salt buffers as followed: 10 times with 600 µl buffer A (0.1% SDS, 2 mM EDTA, 20 mM Tris HCl pH8, 1% Triton X-100, 500 mM NaCl), 8 times with 600 µl buffer B (0.1% SDS, 2 mM EDTA, 20 mM Tris HCl pH8, 1% Triton X-100, 1 M NaCl), 3 times with 600 µl TE (10 mM Tris HCl H8, 1 mM EDTA) buffer. Recovered DNA was amplified with custom Taqman Assays (Applied Biosystems) spanning a predicted hypoxia response element (HRE) site at −1691 bp of the GLUT1 proximal promoter (GLUT1 fwd: CAAATGTGTGGATGTGAGTTGC; GLUT1 rev: CCATCACGGTCCTTCTTCATG; GLUT1 probe: AGGCTGAGCGTGTAAA).…”
Section: Methodsmentioning
confidence: 99%
“…ChIP experiments were performed with HIF-2α (Novus Biologicals) or immunoglobulin G (IgG) antibody (Santa Cruz) as previously described [20], [21] except that immuno-complexes were washed using high-salt buffers as followed: 10 times with 600 µl buffer A (0.1% SDS, 2 mM EDTA, 20 mM Tris HCl pH8, 1% Triton X-100, 500 mM NaCl), 8 times with 600 µl buffer B (0.1% SDS, 2 mM EDTA, 20 mM Tris HCl pH8, 1% Triton X-100, 1 M NaCl), 3 times with 600 µl TE (10 mM Tris HCl H8, 1 mM EDTA) buffer. Recovered DNA was amplified with custom Taqman Assays (Applied Biosystems) spanning a predicted hypoxia response element (HRE) site at −1691 bp of the GLUT1 proximal promoter (GLUT1 fwd: CAAATGTGTGGATGTGAGTTGC; GLUT1 rev: CCATCACGGTCCTTCTTCATG; GLUT1 probe: AGGCTGAGCGTGTAAA).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, down-and up-modulation of CSDA levels consistently corresponded to variations of HBG expression levels: CSDA knockdown induced by RNAi resulted in significantly increased expression of HBG genes, whereas its overexpression was associated with reduced HBG mRNA levels. Also, chromatin immunoprecipitation (ChiP) analysis in K562 cells showed that CSDA interacts with this promoter region, thus confirming that CSDA modulates HBG expression at the transcriptional level [18]. Subsequently, it has been proposed that NF-kB and histone deacethylase 2 (HDAC2) interact with CSDA to form a multiprotein complex which take part to the regulation of HBG2 expression by modulating local chromatin conformation [23], thus highlighting the relevance of the role played by CSDA in fetal globin gene expression and shedding novel light on the molecular mechanisms involved in globin gene switching (Figure 3).…”
Section: Cold-shock Domain Protein a (Csda)mentioning
confidence: 71%
“…CSDA acts as a repressor of many cellular genes including the human granulocytemacrophage colony-stimulating factor (GM-CSF), an important hematopoietic growth factor [17]. More recently, it has been demonstrated that CSDA acts as a repressor of fetal globin gene expression by binding a region −200 bp upstream of the HBG2 gene [18] (Figure 2). This region consists of alternating homopurine and homopyrimidine tracts generating an H-DNA structure [19].…”
Section: Cold-shock Domain Protein a (Csda)mentioning
confidence: 99%
See 1 more Smart Citation
“…It had been found that the BCL11A locus codifies for a transfactor acting as repressor of fetal globin genes (Xu et al, 2011). Recently, another repressor of fetal globin genes, the Cold Shock Domain Protein A or CSDA, has been identified and characterized (Petruzzelli et al, 2010). Therefore, both these two factors may be directly involved in the switching of globin gene expression through silencing of the transcriptional activity of globin genes in adult life, although additional studies are required in order to define better their role in the regulation of this complex mechanism of gene expression.…”
Section: High Persistence Of Fetal Hemoglobin (Hpfh)mentioning
confidence: 99%